2022
DOI: 10.37287/ijnhs.v3i1.973
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Indeks Massa Tubuh dengan Tekanan Darah pada Orang Dewasa

Abstract: Permasalahan yang paling sering terjadi di masyarakat dengan jumlah penderita yang selalu melonjak naik hampir tiap tahunnya adalah penyakit hipertensi. Salah satu pemicu yang mempengaruhi tekanan darah adalah gaya hidup sedentary yang menyebabkan kegemukan. Penelitian ini bermaksud untuk melihat apakah ada hubungan indeks massa tubuh dengan hipertensi pada orang dewasa. Penelitian ini menggunakan pendekatan observasional dengan desain deskriptif korelas dengan mengambil sampel 110 orang dewasa berusia 25-50 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The results of this research showed that the majority were women, with 26 (86.7%) respondents compared to men. This research was following research by (Abineno and Malinti, 2022) in Ponain Village which showed that the majority of hypertension respondents were women with a total of 61 (55.5%) respondents. Lower estrogen levels after menopause may partly explain lower arterial compliance and increased risk of hypertension in older women (Abramson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this research showed that the majority were women, with 26 (86.7%) respondents compared to men. This research was following research by (Abineno and Malinti, 2022) in Ponain Village which showed that the majority of hypertension respondents were women with a total of 61 (55.5%) respondents. Lower estrogen levels after menopause may partly explain lower arterial compliance and increased risk of hypertension in older women (Abramson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, body mass index (BMI) is a direct, economical, and non-intrusive approach. Body Mass Index (BMI) fails to account for variations in muscle mass and body fat distribution [19,20].…”
Section: Body Mass Indexmentioning
confidence: 99%
“…The more you get older, the greater the risk of hypertension. This is caused by changes in the structure of blood vessels, such as the narrowing of the lumen, as well as the walls of blood vessels becoming stiff and their elasticity reduced, thereby increasing hypertension (Abineno & Malinti, 2022). Based on the gender of the elderly who follow prolanis, the most are women, namely 31 people (86.1%)…”
Section: Nutritional Stagementioning
confidence: 99%